2012
DOI: 10.3892/ijo.2012.1622
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free microRNAs in urine as diagnostic and prognostic biomarkers of bladder cancer

Abstract: Abstract. miRNAs are small, non-coding RNAs that play important roles in various biological processes. The aims of our study were to investigate whether cell-free miRNAs can be measured in urine samples and might be an accurate biomarker of bladder cancer. Datasets of GSE20418 and GSE19717 were used for analysis, and two miRNAs, miR-145 and miR-200a, were selected for study. A total of 207 patients with primary transitional cell carcinoma of the urinary bladder and 144 healthy normal controls were enrolled. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(88 citation statements)
references
References 27 publications
3
82
1
1
Order By: Relevance
“…MiR-145 acts as a tumor inhibitor by inhibiting the expression of many oncogenic genes. For example, miR-145 inhibits the development and angiogenesis of tumors by acting on insulin receptor substrate-1, c-Myc, and p70S6K1 [12][13][14]16]. MiR-145 plays a role in p53-initiated cell cycle arrest by negatively regulating p21 [19][20][21].…”
Section: Resultsmentioning
confidence: 99%
“…MiR-145 acts as a tumor inhibitor by inhibiting the expression of many oncogenic genes. For example, miR-145 inhibits the development and angiogenesis of tumors by acting on insulin receptor substrate-1, c-Myc, and p70S6K1 [12][13][14]16]. MiR-145 plays a role in p53-initiated cell cycle arrest by negatively regulating p21 [19][20][21].…”
Section: Resultsmentioning
confidence: 99%
“…Even after seven cycles of freezing and thawing or a 72 h long storage at room temperature, miRNA levels in the urine remained unchanged. 56 Generally, urine samples contain lower levels of proteins than blood-based samples, thus reducing protein interference during RNA isolation. However, in the kidney, there is a large amount of nucleases, including RNases, which could lead to the degradation of long-chain RNAs that are unstable in these conditions.…”
Section: Rationale and Feasibility Of Mirnas Detection In Urine Samplementioning
confidence: 99%
“…In contrast to isolated total RNA, the RNA integrity number (RIN value) of which decreased considerably after dilution in water and treatment at 80 C for up to 4 h; this had almost no influence on the stability of cfmiRNA when measured by qPCR [7,86]. Also repetitive freezing and thawing of miRNA samples [87] or of urine samples which were either subjected to seven freeze/thaw cycles or were incubated at room temperature for up to 3 days did not change the amount of miRNA detectable by qPCR [88]. It was also shown that stool derived miRNAs that are either bound to cell membranes or are inside exosomes are rather stable [89].…”
Section: Mirnamentioning
confidence: 99%